Prediksi Ketepatan Klasifikasi Status Predikat Lulusan Program Sarjana FMIPA Universitas Mulawarman Menggunakan Regresi Logistik Biner dan Neural Networks - Khasanah, Lisa Dwi Nurul; Fathurahman, M.; Hayati, Memi Nor (EKSPONENSIAL, 2024)
Classification is a learning technique for identifying categorical groups from a data set whose group member categories are known. Several methods that can be used in classification include binary logistic regression and neural networks. This research aims to compare the prediction results for the accuracy of the classification of predicate status for graduates of the FMIPA Mulawarman University undergraduate program in 2021. In the binary logistic regression method, the model parameters are estimated using the maximum likelihood estimation and Fisher scoring iteration methods. The neural networks used the backpropagation algorithm. The results of the research show that the classification accuracy using the confusion matrix obtained with binary logistic regression and neural networks is the same, namely 87.5%.